Aspergillus niger production of cellulases by solid‑state fermentation - Rodríguez-Zúñiga, Ursula Fabiola; Farinas, Cristiane Sanchez; Bertucci Neto, Victor; Couri, Sonia; Crestana, Silvio (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate cellulase enzyme production by the filamentous fungus Aspergillus niger by solid-state fermentation of different substrates. The solid substrates sugarcane bagasse, wheat bran, soybean meal, and their mixtures were evaluated. The effects of substrate moisture contents (60, 70, and 80% in humid basis) and of the supplementation with culture media: sucrose, basic Mandels & Weber, modified Mandels & Weber, with the addition of carboxymethyl cellulose, and Czapeck Dox, were evaluated in substrate with 90% bagasse and 10% soybean meal. The highest total cellulose and endoglucanase activities, in wheat bran, were obtained after 72 hours: 0.4 and 21.0 IU g-1, respectively. There was an expressive increase in enzymatic activities as the proportion of bran in the substrate increased, in comparison to fermentation with sugarcane bagasse only. The 50% moisture content was insufficient to fully hydrate sugarcane bagasse, and the ideal humidity varies according to the medium used for supplementation and is between 70 and 80%. The modified Mandels &Weber medium shows the best result as an inductor of enzymatic activity.